DESAIN DAN IMPLEMENTASI JARINGAN WIRELESS POINT TO MULTIPOINT (PTMP) DENGAN PROTOKOL NV2 DAN MODE BRIDGE - Juwari Juwari; Wartono Wartono (LPPM Politeknik Pratama Kendal, 2025)
Currently, the IEEE 802.11 standard protocol is prone to interference. Therefore, a strategy is needed to reduce or avoid intervention. Using the Nv2 Protocol at the 5 GHz frequency with bridge mode on the Point to Multipoint Network (PTMP) can be used as a solution to avoid interference. The method in this screening begins with a location survey then continues with needs analysis, topology design, network installation, network configuration and at the final stage testing is carried out. The results of the study showed that the connection between the two clients resulted in ping with a 0% loss package and the results were very good. The signal strength from the AP Bridge side to client 1 is -63 Db to client 2 is -54 Db. AP Client 1 with a Signal Strength of -63/-62dBm, Tx/Rx CCQ 9/18%. AP Client 2 with Signal Strength -54/-56 dBm, Tx/Rx CCQ 40/35%.